Studies of Vanadyl(IV) Complexes with Schiff Bases of 2-Aminopyridine - Arora, Kishor; Sharma, D.P.; Pathak, M.C.; Goyal, R.C. (Asian Journal of Chemistry, 2010)
A series of oxovanadium(IV) complexes with Schiff of 2-aminopyridine, i.e., 2-N-[benzalidene] aminopyridine (BAPY), 2-N-[p-dimethyl benzalidine] aminopyridine (PABAPy) and a thiosemicarbazone ligand, i.e., 2-N-[acetylacetone] aminopyridine thiosemicarbazone (AcAyPyT) have been synthesized. On the basis of analytical and spectral studies complexes were found to have general composition VOX2L2 (X = Cl–, Br–, L = BAPy or PABAPy) and VOX2·AcAcPyT (X = Cl– or Br–). V-atom is 5 or 6 coordinated depending upon the anion present. NMR and antifungal studies, of representative complexes have been done successfully.